The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1038/npp.2011.34
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of CB2 Cannabinoid Receptor Induces Schizophrenia-Related Behaviors in Mice

Abstract: The possible role of the CB 2 receptor (CB 2 r) in psychiatric disorders has been considered. Several animal models use knockout (KO) mice that display schizophrenia-like behaviors and this study evaluated the role of CB 2 r in the regulation of such behaviors. Mice lacking the CB 2 r (CB 2 KO) were challenged in open field, light-dark box, elevated plus-maze, tail suspension, step down inhibitory avoidance, and pre-pulse inhibition tests (PPI). Furthermore, the effects of treatment with cocaine and risperidon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
134
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(153 citation statements)
references
References 97 publications
10
134
0
3
Order By: Relevance
“…This is consistent with our previous findings that systemic or local administration of JWH133 into the nucleus accumbens inhibits cocaine self-administration (22), and that transgenic up-regulation of brain CB 2 Rs attenuates cocaine self-administration and cocaine-induced increased locomotion (19). The present findings are also congruent with recent reports that brain CB 2 Rs have important roles in other DArelated functions and/or CNS disorders (12,25,51,52).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with our previous findings that systemic or local administration of JWH133 into the nucleus accumbens inhibits cocaine self-administration (22), and that transgenic up-regulation of brain CB 2 Rs attenuates cocaine self-administration and cocaine-induced increased locomotion (19). The present findings are also congruent with recent reports that brain CB 2 Rs have important roles in other DArelated functions and/or CNS disorders (12,25,51,52).…”
Section: Discussionsupporting
confidence: 93%
“…This finding is supported by recent studies demonstrating that systemic administration of the CB 2 R agonist O-1966 inhibited cocaine-induced conditioned place preference in WT mice, but not in CB 2 −/− mice (23), and that increased CB 2 R expression in mouse brain attenuates cocaine self-administration and cocaine-enhanced locomotion (19). In addition, brain CB 2 Rs may be involved in several DA-related CNS disorders, such as Parkinson's disease (24), schizophrenia (25), anxiety (26), and depression (27). The cellular mechanisms underlying CB 2 R modulation of DA-related behaviors and diseases are unclear, however.…”
mentioning
confidence: 78%
“…Several studies in animal models have demonstrated that dopaminergic activation (eg, apomorphine treatment, deletion of DAT) induces PPI disruption that is blocked by dopaminergic antagonists such as typical or atypical antipsychotics (Swerdlow and Geyer, 1993). In our study, treatment with risperidone or haloperidol did not modify PPI values in CB1KO mice, whereas a tendency toward an impairment effect was obtained in WT mice as shown previously (Ortega-Alvaro et al, 2011). Interestingly, the administration of the psychostimulant methylphenidate significantly improved PPI in CB1KO mice.…”
Section: Cb1 Receptors and Sensorimotor Gating Regulationsupporting
confidence: 84%
“…As our knowledge about the neurobiology of preattentional deficit-related disorders from human studies is limited, it is quite difficult to decide which model best represents the PPI disruption of a specific psychiatric disorder. Recently, we used a phenotype-based approach in CB2r knockout (CB2KO) mice to explore the role of the CNR2 gene in a particular phenotype related to schizophrenia because of the amelioration effect achieved with the risperidone treatment (Ortega-Alvaro et al, 2011). In the case of the CNR1 gene, we found a different behavioral phenotype in CB1r knockout (CB1KO) mice.…”
Section: Introductionmentioning
confidence: 99%
“…2 In a number of additional cell types under disease conditions, CB 2 R expression is greatly up-regulated. 3 The richness of CB 2 R involvement has positioned the receptor as an attractive therapeutic target for treating an array of pathologies, such as cancers, 4,5 neurodegenerative diseases, 2,6 inflammation, 7,8 pain, 9 osteoporosis, 10 immunological disorders, [11][12][13] and drug abuse. 14 As such, there has been an explosion of research over the past 12 years that focused on the biology and therapeutic promises of CB 2 R. However, the precise role of CB 2 R in the regulation of diseases remains unclear.…”
Section: Introductionmentioning
confidence: 99%